PENGARUH BELANJA KESEHATAN TERHADAP PRODUKTIVITAS TENAGA KERJA DI PROVINSI JAWA TENGAH TAHUN 2008-2010 - Marselina S, Dwinda; Sugiyanto, FX (Diponegoro Journal of Economics, 2013)
Health has a very important role in creating quality human resources. Public health condition closely related to the government's attention to government expenditure spent on health. While spending on health increase, the labor productivity is increasing. However, the relationship between health expenditure on labor productivity in the province of Central Java is no direct relationship. The relationship was formulated following the chain rule that based on the theory of production. There is a variable health in chain-rule was measured using infant mortality. This study aimed to estimate the relationship patterns of health expenditure on labor productivity in Central Java province during the years 2008-2010, and to estimate how much health expenditures influence labor productivity in Central Java province during the years 2008-2010. By using panel data techniques, this study uses 35 district / town in Central Java as the sample. Based on the results of data processing, the researcher conclude there is a significant and positive effect between health expenditure on labor productivity in the District of Central Java during the years 2008-2010. While health status as measured by infant mortality and significant effect on labor productivity. Thus, the pattern of the relationship between health expenditure on labor productivity does not follow the principles of Chain-Rule.